Zakat Management Paradigm: Comparison of Indonesia, Malaysia and Saudi Arabia - Muhammad Anwar Fathoni; Suryani Suryani; Eko Nur Cahyo (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
The obligation of Muslims in zakat is expected to help solve the problem of income distribution among human beings. This article aims to find out the management of zakat in Muslim countries, namely Indonesia, Malaysia and Saudi Arabia. Important findings produced there are differences in the management of zakat in Indonesia, Malaysia and Saudi Arabia. From the side of the law it is known that Indonesia and Malaysia do not require zakat in their laws, something different from Arab Saubi has even developed an online-based zakat collection and tax system. While from the zakat collection system, the policy in Malaysia makes zakat a tax deduction.